Synthesis, Spectral Characterization and in vitro Antidiabetic Properties of Oxovanadium(IV) Complexes with 2-(E)-Pyridin-4-yl[2-(pyridin-2-yl)hydrazinylidene]methylpyridine - Patel, Babbu Lal; Singh, Yogendra Pratap; Patel, R.N.; Singh, P.K. (Asian Journal of Chemistry, 2018)
A series of oxovanadium(IV) complexes [VO(phen)(L)](NO3)2 (1), [VO(dimphen)(L)](NO3)2 (2), [VO(bpy)(L)](NO3)2 (3) and [VO(bpybenImH)(L)](NO3)2 (4) with mixed ligands, a tridentate N,N,N-donor Schiff base ligand [viz., 2-(E)-pyridin-4-yl[2-(pyridin-2-yl)hydrazinylidene]methylpyridine] (L) and a bidentate N,N ligand [viz., 1,10-phenanthroline (phen), 4,7-dimethyl-1,10-phenanthroline (dimphen), 2,2′-bipyridyl (bpy) and 2-(2-pyridyl)benimidazole (bipybenImH)], have been synthesized and characterized by elemental analysis, UV-visible spectroscopy, Fourier transform IR spectroscopy, EPR spectroscopy, cyclic voltammetric and differential pulse voltammetric techniques. The oxidation state of V(IV) with d1 configuration was confirmed by EPR spectroscopy. The complexes were also tested for in vitro antidiabetic activity. Moderate α-glucosidase inhibitions are shown by these complexes. This suggested that the complexes may be promising candidates as antidiabetic agents.